Nineteenth Century French Military Sabre - Julien Garry (Acta Periodica Duellatorum, 2020)
Numerous treaties and methods regarding fencing are known today, either written by experts, veterans of sword-masters, or by the ministry or war and its branches: the schools of Joinville and Saumur. Some are destined to horse riders, others to officers. Each of these methods has its own particularities and, due to the abundance of treaties, discerning the qualities, the flaws, and the overall interest of a specific method can seem complicated. An attempt is made below to answer: why were the methods of French saber in the nineteenth century conceived and Why were they made this way, and what connection do they share with the French military world. These texts are compared and analyzed to uncover their function regarding the Army. From this analysis, three types of fencing will emerge, sometimes opposite, sometimes complementary; war fencing: conceived to be applicable on the battlefield – duel fencing (that was less official but still popular in nineteen century France) – and finally, recreational fencing, most often taking the form of a sport.